Educational work as a leading component of the activities of the department of social and humanitarian disciplines - Soloshenko, E. (New Collegium, 2021)
The main stages of the history of the department of social and humanitarian disciplines are briefly sanctified, its long-term experience is analyzed through the prism of teaching and educational activities. Attention is drawn to the role of social and humanitarian disciplines in the process of forming general and universal competencies of a modern specialist. Soft skills have a fairly wide range: linguistic, social, entrepreneurial, communicative, life cognitive and informational, etc.The ways of formation of these competence components in students in the study of the disciplines of the humanitarian cycle are analyzed. It is noted that all academic disciplines that are taught at the department have and successfully embody the educational component. The author analyzes the activities that contribute to the implementation of national-patriotic, spiritual, legal, moral and other types of education in a modern university both during classes and outside the classroom.Emphasis is placed on cooperation with the Center for Military-Patriotic Education of KNUSA, in particular, the implementation of the principle of historical and social memory. The Gender Education Center complements the educational process with coverage of gender issues. Relevant aspects of the education of modern students, which the department embodies by holding round tables by the Student Scientific Society of the Clio Department, conversations in dormitories and informing during classrooms, is the coverage of the process of European integration, the importance of countering racism, xenophobia and extremism. The necessity of the institution of curators-mentors in educational work with students is emphasized. Throughout its history, the educational component of the work of the Department of Social and Humanitarian Disciplines has remained unchanged – the formation of eternal human values, a worthy person and citizen of Ukraine.